NiBP / G-based magnesium hydride hydrogen storage material as well as preparation method and application thereof

By introducing NiBP/G catalyst into magnesium hydride and performing doping by high-energy ball milling, the problems of high hydrogen release temperature and low hydrogen absorption and release reaction rate of magnesium hydride were solved, and lower hydrogen release temperature and higher reaction rate were achieved. , improving the cycle performance of hydrogen storage materials.

CN119349507APending Publication Date: 2025-01-24HENAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411588941.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

As a hydrogen storage material, magnesium hydride has problems with high hydrogen release temperature and low hydrogen release reaction rate, which limits its large-scale commercial application.

Method used

By introducing NiBP/G catalyst into magnesium hydride and using high-energy ball milling method for doping, the hydrogen release temperature is reduced and the hydrogen absorption and release reaction rate is increased.

Benefits of technology

It achieves a lower hydrogen release temperature than magnesium hydride, increases the hydrogen absorption and release reaction rate, reduces material agglomeration through the addition of graphene, and improves cycle performance and utilization of hydrogen storage materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a NiBP / G-based magnesium hydride hydrogen storage material as well as a preparation method and application thereof, and belongs to the technical field of magnesium-based hydrogen storage materials. The hydrogen storage material is prepared from magnesium hydride and NiBP / G through ball milling. The preparation method comprises the following steps: firstly, uniformly mixing graphene, water, nickel chloride hexahydrate and sodium hypophosphite; and adding a sodium borohydride solution in a low-temperature environment for reduction to obtain the NiBP / G catalyst. Finally, the NiBP / G catalyst and magnesium hydride are subjected to ball milling, and the magnesium hydride hydrogen storage material based on NiBP / G can be prepared. The hydrogen storage material has excellent performance, compared with commercial magnesium hydride, the initial hydrogen desorption temperature is reduced by 315 DEG C, the initial hydrogen desorption temperature is reduced by 35 DEG C compared with ball-milled magnesium hydride, the hydrogen desorption amount reaches 6.0 wt% at the temperature of 310 DEG C within 15 minutes, the hydrogen absorption amount reaches 5.0 wt% at the temperature of 150 DEG C within 45 minutes, the performance is not attenuated after 50 times of circulation at the temperature of 300 DEG C, and the hydrogen storage material has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen storage materials, and in particular, relates to a NiBP / G-based magnesium hydride hydrogen storage material and a preparation method and application thereof. Background Art

[0002] As global energy, environment and climate change issues become increasingly prominent, sustainable development has become a major issue in the new era. Hydrogen energy is regarded as an ideal energy source due to its inherent advantages such as high energy density, abundant resources, zero pollution, zero carbon emissions, storability and renewability. However, to achieve the commercial development of hydrogen energy, it is necessary to reduce the cost of hydrogen production, improve the efficiency of hydrogen storage systems, and choose appropriate transportation methods. At present, the promotion of hydrogen application technology is still a top priority. Therefore, finding efficient hydrogen storage materials is a challenging task.

[0003] Among solid-state hydrogen storage materials, MgH2 is considered to be one of the most promising hydrogen storage materials due to its abundant resources, low price, high hydrogen storage capacity (7.6 wt%), and good reversibility. It should be pointed out that although magnesium hydride has the above advantages, it also has many problems. First, the high thermodynamic stability of the Mg-H bond causes the dehydrogenation temperature of MgH2 to be higher than 673 K, corresponding to a dehydrogenation reaction enthalpy of 75 kJ / mol. Secondly, due to the relative difficulty of hydrogen molecule dissociation on the magnesium surface and hydrogen atom recombination on the MgH2 surface, the diffusion rate of hydrogen atoms in Mg, especially in the MgH2 matrix, is slow, resulting in difficulty in activating magnesium-based hydrogen storage materials and poor hydrogen absorption and desorption kinetics, which limits the large-scale commercial application of magnesium hydride.

[0004] So far, the methods for improving the kinetic and thermodynamic properties of magnesium-based hydrogen storage mainly include alloying, nano-sizing, and adding catalysts. Among them, adding catalysts is the most effective method to improve the performance of magnesium hydride. Based on this, this application was developed. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and to provide a magnesium hydride hydrogen storage material based on NiBP / G in view of the shortcomings of the current magnesium hydride hydrogen storage material. The hydrogen storage material has a lower hydrogen desorption temperature than magnesium hydride, and improves the hydrogen absorption / desorption reaction rate. Moreover, the addition of graphene can reduce material agglomeration, improve cycle performance, and increase the utilization rate of the hydrogen storage material.

[0006] The present invention also provides a preparation method of the NiBP / G-based magnesium hydride hydrogen storage material and its application.

[0007] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a magnesium hydride hydrogen storage material based on NiBP / G, comprising the following steps: (1) graphene and deionized water are uniformly mixed to obtain a graphene dispersion, nickel chloride hexahydrate and sodium hypophosphite are added to the graphene dispersion to dissolve to obtain a reaction solution A; sodium borohydride aqueous solution is added to the reaction solution A under a low temperature environment, and then a reduction reaction is carried out. After the reaction is completed, the NiBP / G catalyst is obtained after washing and drying; (2) Preparation of NiBP / G-based magnesium hydride hydrogen storage material: By high-energy ball milling, the NiBP / G catalyst prepared in step (1) and purchased commercial magnesium hydride are ball milled and mixed under certain conditions according to a certain doping amount to obtain a NiBP / G-based magnesium hydride hydrogen storage material.

[0008] Specifically, in step (1), the molar ratio of nickel chloride hexahydrate to sodium hypophosphite can be 1:6-8. The amount of sodium borohydride added can account for 94-96% of the mass of nickel chloride hexahydrate. The amount of graphene added can account for 5-7% of the mass of nickel chloride hexahydrate.

[0009] Furthermore, in step (1), the reduction reaction refers to a reaction at room temperature for 8-12 hours. The low temperature environment refers to a temperature of 0-5°C.

[0010] Specifically, in step (2), the NiBP / G catalyst doping amount can account for 3-15% of the mass of the hydrogen storage material. In step (2), the ball milling conditions are: in a hydrogen environment, the ball-to-material ratio is 35-45:1, the rotation speed is 300-500 rpm, and the ball milling time (effective time) is 2-4 h. Forward and reverse rotation is 4-6 min, and rest is 1 min.

[0011] The present invention provides a magnesium hydride hydrogen storage material based on NiBP / G prepared by the above-mentioned preparation method, which is prepared by ball milling NiBP / G and magnesium hydride; the NiBP / G is directly prepared by reduction at low temperature. The NiBP / G is a nanoparticle stacking structure with a particle size of 50-150 nm; the nickel nanoparticles are loaded on the surface of graphene.

[0012] The present invention also provides the application of the NiBP / G-based magnesium hydride hydrogen storage material in the field of hydrogen storage. When the NiBP / G doping amount is 10 wt%, the initial dehydrogenation temperature is 115 ° C. At 310 ° C, the dehydrogenation amount reaches 6.0 wt% in 15 minutes, and at 150 ° C, the hydrogen absorption amount reaches 5.0 wt% in 45 minutes. There is no performance degradation after 50 cycles at 300 ° C.

[0013] The technical effects of the present invention have been tested experimentally, and the specific contents are as follows: The present invention has known through XRD and XPS detection that Ni in NiBP / G exists in a single substance form, and B and P exist in an amorphous form.

[0014] According to SEM and EDS tests, NiBP / G uses spherical graphene as a carrier to load Ni particles with a size of 50-150 nm, and each element is evenly distributed.

[0015] XRD detection shows that in the process of ball milling, dehydrogenation and re-absorption of hydrogen in the MgH2-10 wt%NiBP / G hydrogen storage material, the Mg element exists in the forms of MgH2, Mg, MgO, Mg2Ni, MgH2 and Mg2NiH4, respectively, while the Ni element exists in the forms of Ni, Mg2Ni and Mg2NiH4, respectively.

[0016] The present invention is tested by programmed temperature rise and it is found that the optimal doping amount of NiBP / G is 10 wt%, and the initial dehydrogenation temperature is 115 °C, which is 35 °C lower than that of ball-milled magnesium hydride.

[0017] The isothermal hydrogen absorption and desorption test of the present invention shows that the MgH2-10 wt% NiBP / G hydrogen storage material absorbs 5.0 wt% of hydrogen in 45 minutes at 150 °C, and releases 6.0 wt% of hydrogen in 15 minutes at 310 °C.

[0018] The cyclic performance test of the present invention shows that the performance of the MgH2-10 wt%NiBP / G hydrogen storage material does not decay after 50 cycles at 300 °C.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1) In the present invention, graphene is selected as a carrier, which has the functions of dispersion and co-catalysis.

[0020] 2) The NiBP / G prepared in the present invention has a good catalytic effect, and NiBP / G helps hydrogen dissociation and provides more active sites.

[0021] 3) The raw materials used in the present invention are cheap, the synthesis steps are simple, and the experimental time period is short. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the XRD pattern of NiBP / G in Example 1; Figure 2 The SEM (A) and EDS images of NiBP / G in Example 1; B, C, and D are element distribution diagrams of C, Ni, and P, respectively; Figure 3 is the XPS graph of NiBP / G in Example 1; Figure 4 is the XRD pattern of the MgH2-10 wt%NiBP / G hydrogen storage material in Example 1; Figure 5XRD diagram of hydrogen release and hydrogen reabsorption of MgH2-10 wt%NiBP / G hydrogen storage material in Example 1; Figure 6 TPD diagrams of MgH2, comparative example 1 Ball milled MgH2, example 1 MgH2-10 wt%NiBP / G, example 2 MgH2-7 wt%NiBP / G and example 3 MgH2-13 wt%NiBP / G hydrogen storage materials; Figure 7 is the isothermal hydrogen release diagram of the MgH2-10 wt%NiBP / G hydrogen storage material at different temperatures in Example 1; Figure 8 is the isothermal hydrogen absorption diagram of the MgH2-10 wt%NiBP / G hydrogen storage material at different temperatures in Example 1; Fig. 9 This is a cycle test diagram of the MgH2-10 wt%NiBP / G hydrogen storage material at 300 °C in Example 1; Fig.10 Isothermal hydrogen release diagrams of Ball milled MgH2 of Comparative Example 1, MgH2-10 wt%G of Comparative Example 2 and MgH2-10wt%NiBP / G of Example 1. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0024] In the following examples, the raw materials used are all common commercial products that can be directly purchased or can be prepared using conventional techniques in the art.

[0025] Room temperature refers to 25±°C.

[0026] Example 1 A method for preparing a magnesium hydride hydrogen storage material based on NiBP / G comprises the following steps: (1) Under stirring conditions, 75 mg of graphene and 20 ml of deionized water were mixed evenly to obtain a graphene dispersion, and then 1.1897 g (0.005 mol) of nickel chloride hexahydrate and 3.1797 g (0.036 mol) of sodium hypophosphite were added to the graphene dispersion to dissolve to obtain a reaction solution A. 1.1349 g of sodium borohydride was added to 20 ml of deionized water to prepare a solution B with a mass fraction of about 5.4 wt%. Under a low temperature environment of 0-5 °C, solution B was slowly added dropwise to reaction solution A. After the addition was completed, the solution was stirred at room temperature for 10 h for reduction reaction. After the reaction was completed, the reactants were rinsed with deionized water and ethanol, respectively, and then filtered and dried at 60 °C under vacuum conditions for 24 h to obtain NiBP / G catalyst; (2) Preparation of NiBP / G-based magnesium hydride hydrogen storage material: By high-energy ball milling, 0.1 g of NiBP / G prepared in step (1) and 0.9 g of commercial magnesium hydride were ball milled in a hydrogen environment at a ball-to-material ratio of 40:1, a rotation speed of 400 rpm, a ball milling time of 3 h, a forward and reverse rotation of 5 min, and an interval of 1 min, with a NiBP / G doping amount of 10 wt%. Thus, a NiBP / G-based magnesium hydride hydrogen storage material was obtained (the obtained material was named MgH2-10 wt%NiBP / G hydrogen storage material).

[0027] In order to verify the microstructure of NiBP / G, SEM test was carried out. In order to verify the composition of NiBP / G, XRD test and XPS test were carried out.

[0028] Figure 1 The XRD diagram of NiBP / G is given; it can be seen from the figure that diffraction peaks of Ni and graphene appear.

[0029] Figure 2 The SEM and EDS images of NiBP / G in Example 1 are given; it can be seen from the images that the metal particles are tightly anchored on the surface of G, and the EDS spectrum shows that the Ni, P and C elements are uniformly dispersed in the NiBP / G catalyst.

[0030] Figure 3 The XPS graph of NiBP / G in Example 1 is given; it can be seen from the graph that B and P exist in the catalyst in an amorphous structure.

[0031] In order to prove the composition of MgH2-10 wt% NiBP / G, XRD test was carried out.

[0032] Figure 4 The XRD pattern of the MgH2-10 wt%NiBP / G hydrogen storage material in Example 1 is given; it can be seen from the figure that during the ball milling process, Ni participates in the reaction and generates Mg2NiH4 in situ.

[0033] In order to demonstrate the effect of NiBP / G and its different doping amounts on the dehydrogenation performance in NiBP / G-based magnesium hydride hydrogen storage materials, a heating rate of 2 °C / min and a final temperature of 450 °C were used to perform a dehydrogenation test. Figure 6 As shown in Table 1, MgH2-10 wt%NiBP / G has an initial dehydrogenation temperature of 115 °C and a final dehydrogenation amount of 5.71 wt%. When the NiBP / G doping amount is 10 wt%, it has the best performance.

[0034] Table 1 Summary of initial dehydrogenation temperature and dehydrogenation amount at different NiBP / G doping levels Figure 5 The XRD patterns of hydrogen release and hydrogen reabsorption of the MgH2-10 wt% NiBP / G hydrogen storage material in Example 1 are given; it can be seen from the figure that their diffraction peaks after one dehydrogenation and 50 dehydrogenations are basically consistent, and during the hydrogenation and dehydrogenation process, in addition to the conversion between MgH2 and Mg, a reversible stable Mg2NiH4 / Mg2Ni phase is generated, which can effectively reduce the hydrogen absorption / desorption temperature of the hydrogen storage system as a "hydrogen pump".

[0035] Figure 6 TPD diagrams of MgH2, comparative example 1 Ball milled MgH2, example 1 MgH2-10 wt%NiBP / G, example 2 MgH2-7 wt%NiBP / G and example 3 MgH2-13 wt%NiBP / G hydrogen storage materials are given; it can be seen from the diagram that the best performance is achieved when the NiBP / G doping amount is 10 wt%.

[0036] Comparative Example 1 In order to demonstrate the effect of NiBP / G as a catalyst on the hydrogen release performance of magnesium hydride, a comparative example 1 is provided to prepare a magnesium hydride hydrogen storage material with a NiBP / G doping amount of 0 wt%.

[0037] A method for preparing a magnesium hydride hydrogen storage material with a NiBP / G doping amount of 0 wt%, wherein the steps not specifically described are the same as those in Example 1, except that: step (1) is not required, and step (2) is directly performed, and in step 2, NiBP / G is not added, that is, only 1 g of commercial magnesium hydride MgH2 is weighed and ball milled, and the obtained material is named Ballmilled MgH2.

[0038] The results of the heating and hydrogen release test of Ball milled MgH2 are as follows: Figure 6As shown in Table 1, the initial dehydrogenation temperature is 150 °C. The test results compared with magnesium hydride show that ball milling has two effects on the dehydrogenation performance of MgH2: 1. The initial dehydrogenation temperature of MgH2 was reduced from 430 °C to 150 °C, a decrease of 280 °C, which improved the dehydrogenation performance; 2. The final amount of hydrogen released was reduced from 7.4 wt% to 6.43 wt%, which reduced the amount of hydrogen released.

[0039] Comparison of the ball milled MgH2 test results with those of Example 1 shows that the catalyst has two effects on the hydrogen desorption performance of MgH2: 1. The initial dehydrogenation temperature is reduced from 150 °C of Ball milled MgH2 to 115 °C of Example 1, with a decrease of 35 °C, which improves the dehydrogenation performance; 2. The final hydrogen release amount was reduced from 6.43 wt% of Ball milled MgH2 to 5.71 wt% of Example 1, which reduced the hydrogen release performance.

[0040] Example 2 A method for preparing a magnesium hydride hydrogen storage material with a NiBP / G doping amount of 7 wt%, wherein the steps not specifically described are the same as those in Example 1, except that in step 2, 0.07 g of the NiBP / G prepared in step (1) and 0.93 g of purchased commercial magnesium hydride are ball-milled, i.e., the NiBP / G doping amount is 7 wt%, and the obtained material is named MgH2-7 wt%NiBP / G.

[0041] The results of the temperature rise hydrogen release test of MgH2-7 wt%NiBP / G are as follows: Figure 6 As shown in Table 1, the initial dehydrogenation temperature is 150 °C. Compared with the test results of Example 1, it can be seen that reducing the doping amount of NiBP / G from 10 wt% to 7 wt% has two effects on the dehydrogenation performance of MgH2: 1. The initial dehydrogenation temperature was increased from 115 °C in Example 1 to 150 °C in Example 2, with an increase of 35 °C, which reduced the dehydrogenation performance. However, compared with the initial dehydrogenation temperature of 430 °C of pure magnesium hydride MgH2 in Comparative Example 1, the dehydrogenation performance was still improved; 2. The final hydrogen release amount increased from 5.71 wt% in Example 1 to 5.88 wt% in Example 2, improving the hydrogen release performance.

[0042] Example 3 A method for preparing a magnesium hydride hydrogen storage material with a NiBP / G doping amount of 13 wt%, wherein the steps not specifically described are the same as those in Example 1, except that in step 2, 0.13 g of the NiBP / G prepared in step (1) and 0.87 g of purchased commercial magnesium hydride are ball-milled, i.e., the NiBP / G doping amount is 13 wt%, and the obtained material is named MgH2-13 wt%NiBP / G.

[0043] The results of the temperature rise hydrogen release test of MgH2-13 wt%NiBP / G are as follows: Figure 6 As shown in Table 1, the initial dehydrogenation temperature is 160 ° C. Compared with the test results of Example 1, it can be seen that increasing the doping amount of NiBP / G from 10 wt% to 13 wt% has two effects on the dehydrogenation performance of MgH2: 1. The initial dehydrogenation temperature of MgH2 is increased from 115°C in Example 1 to 160°C in Example 3, with an increase of 45°C, which reduces the dehydrogenation performance. However, compared with the initial dehydrogenation temperature of 430°C of pure magnesium hydride MgH2 in Comparative Example 1, the dehydrogenation performance is still improved; 2. The final hydrogen release amount was reduced from 5.71 wt% in Example 1 to 5.21 wt% in Example 3, which reduced the hydrogen release performance.

[0044] Comparative Example 2 A method for preparing a magnesium hydride hydrogen storage material with a G doping amount of 10 wt%, wherein the steps not specifically described are the same as those in Example 1, except that: in step 2, 0.1 g of purchased graphene and 0.9 g of purchased commercial magnesium hydride are ball-milled, that is, the G doping amount is 10 wt%, and the resulting material is named MgH2-10 wt%G.

[0045] The isothermal hydrogen release test results are as follows: Fig.10 As shown, the target dehydrogenation temperature is 300 ° C. Test results: Compared with magnesium hydride, the addition of graphene has an impact on the dehydrogenation performance of MgH2: at the same temperature, the addition of graphene increases the amount of dehydrogenation and the rate becomes faster.

[0046] The following conclusions can be obtained based on Example 1 and Comparative Example 1, Example 2, Example 3 and Comparative Example 2: 1. Increasing the NiBP / G doping amount will reduce the amount of hydrogen release.

[0047] 2. Graphene plays a role of physical adsorption.

[0048] According to practical application requirements, the hydrogen desorption performance is optimal when the doping amount of NiBP / G is 10 wt%.

[0049] In order to demonstrate the hydrogen absorption and desorption kinetics of MgH2-10 wt%NiBP / G, isothermal hydrogen desorption tests were carried out at different target hydrogen desorption temperatures and isothermal hydrogen absorption tests were carried out at different target hydrogen absorption temperatures, namely, isothermal hydrogen absorption and desorption tests.

[0050] The specific test method of isothermal hydrogen desorption performance test is: raise the furnace body to the target desorption temperature, then put the sample to be tested into the sample tube, and then put the sample tube into the furnace body to perform the isothermal desorption test. The different target desorption temperatures are 330 °C, 310 °C, 290 °C and 270 °C. The test results are as follows: Figure 7 And as shown in Table 2.

[0051] Table 2 Summary of isothermal hydrogen desorption of MgH2-10 wt%NiBP / G at different target desorption temperatures The specific method of isothermal hydrogen absorption test is: first, the sample to be tested is completely dehydrogenated, and then the isothermal hydrogen absorption test is performed at the target hydrogen absorption temperature with an initial hydrogen pressure of 30 bar. The target hydrogen absorption temperatures are 300 °C, 250 °C, 150 °C and 50 °C respectively. The test results are shown in Figure 2. Figure 8 And as shown in Table 3.

[0052] Table 3 Summary of isothermal hydrogen absorption of MgH2-10 wt%NiBP / G at different target hydrogen absorption temperatures In order to test the stability of magnesium hydride hydrogen storage materials based on NiBP / G, a cyclic performance test was conducted on MgH2-10 wt%NiBP / G. The cyclic performance test method is as follows: 50 isothermal hydrogen desorption tests and isothermal hydrogen absorption tests were conducted in sequence under the conditions that the target hydrogen desorption temperature and the target hydrogen absorption temperature were both 300 °C. The cyclic performance test results of MgH2-10 wt%NiBP / G are shown in Figure 2. Fig. 9 shown. Fig. 9 It shows that after 50 cycles, the capacity retention rate of MgH2-10 wt%NiBP / G remains unchanged.

Claims

1. A method for preparing a magnesium hydride hydrogen storage material based on NiBP / G, characterized in that: The following steps are involved: (1) graphene and deionized water are uniformly mixed to obtain a graphene dispersion, nickel chloride hexahydrate and sodium hypophosphite are added to the graphene dispersion to dissolve to obtain a reaction solution A; sodium borohydride aqueous solution is added to the reaction solution A under a low temperature environment, and then a reduction reaction is carried out. After the reaction is completed, the NiBP / G catalyst is obtained after washing and drying; (2) The NiBP / G catalyst prepared in step (1) and commercial magnesium hydride are ball-milled and mixed according to a certain doping amount to obtain a NiBP / G-based magnesium hydride hydrogen storage material.

2. The method for preparing the magnesium hydride hydrogen storage material based on NiBP / G as claimed in claim 1, characterized in that: In step (1), the molar ratio of nickel chloride hexahydrate to sodium hypophosphite is 1:6-8.

3. The method for preparing the NiBP / G-based magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step (1), the amount of sodium borohydride added is 94-96% of the mass of nickel chloride hexahydrate.

4. The method for preparing the NiBP / G-based magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step (1), the reduction reaction is carried out at room temperature for 8-12 hours.

5. The method for preparing the magnesium hydride hydrogen storage material based on NiBP / G as claimed in claim 1, characterized in that: In step (1), the amount of graphene added is 5-7% of the mass of nickel chloride hexahydrate.

6. The method for preparing the NiBP / G-based magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step (1), the low temperature environment refers to a temperature of 0-5 °C.

7. The method for preparing the NiBP / G-based magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step (2), the doping amount of the NiBP / G catalyst accounts for 3-15% of the mass of the hydrogen storage material.

8. The method for preparing the NiBP / G-based magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step (2), the ball milling conditions are: in a hydrogen environment, the ball-to-material ratio is 35-45:1, the rotation speed is 300-500 rpm, and the ball milling time is 2-4 h.

9. A NiBP / G-based magnesium hydride hydrogen storage material prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the NiBP / G-based magnesium hydride hydrogen storage material according to claim 9 in the field of hydrogen storage.